2019
DOI: 10.1101/857466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous generation of face recognition in untrained deep neural networks

Abstract: 11Face-selective neurons are observed in the primate visual pathway and are considered the basis of facial 12 recognition in the brain. However, it is debated whether this neuronal selectivity can arise spontaneously, 13 or requires training from visual experience. Here, we show that face-selective neurons arise 14 spontaneously in random feedforward networks in the absence of learning. Using biologically inspired 15 deep neural networks, we found that face-selective neurons arise under three different network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 14, 2021. ; https://doi.org/10.1101/2021.05.12.443829 doi: bioRxiv preprint system [1,23]. Lastly, consistent with our DNN lesion results (Fig.…”
Section: Possible Caveatssupporting
confidence: 90%
“…The copyright holder for this preprint (which this version posted May 14, 2021. ; https://doi.org/10.1101/2021.05.12.443829 doi: bioRxiv preprint system [1,23]. Lastly, consistent with our DNN lesion results (Fig.…”
Section: Possible Caveatssupporting
confidence: 90%
“…Was a face module formed in the d-AlexNet to support these functions? To answer this question, we searched all the channels in Conv5 of the d-AlexNet, where face-selective channels have been previously identified in the AlexNet (Baek et al, 2019 ). To do this, we calculated the activation of each channel in Conv5 after ReLU in response to each category of the classification dataset, and then identified channels that showed significantly higher response to faces than non-face images with Mann-Whitney U test ( p s < 0.05, Bonferroni corrected).…”
Section: Resultsmentioning
confidence: 99%
“…This study presented a DCNN model of selective visual deprivation of faces. Specifically, we chose the AlexNet as a test platform because of the functional correspondence along the hierarchy between the AlexNet and primates' ventral visual pathway (e.g., Krizhevsky et al, 2012 ; Cadieu et al, 2014 ; Wen et al, 2017 ; Pospisil et al, 2018 ; Baek et al, 2019 ). We found that without genetic predisposition and face-specific visual experiences, DCNNs were still capable of face perception.…”
Section: Discussionmentioning
confidence: 99%
“…Was a face module formed in the d-AlexNet to support these functions? To answer this question, we searched all the channels in Conv5 of the d-AlexNet, where face-selective channels have been previously identified in the AlexNet (Baek, Song, Jang, Kim, & Paik, 2019). To do this, we calculated the activation of each channel in Conv5 after ReLU in response to each category of the classification dataset, and then identified channels that showed significantly higher response to faces than non-face images with Mann-Whitney U test (ps < .05, Bonferroni corrected).…”
Section: Resultsmentioning
confidence: 99%